Kirschner wire as an effective localization tool in UBE discectomy: enhancing segmental localization accuracy and optimizing decompression margins - Changwei Yang; Guangzhu Yan; Kai Luo; Mingyuan Yang; Maoning Fang; Xiaolong Li; Yushu Bai; Qiulin Zhang (Scientific Reports)
Abstract Unilateral biportal endoscopic (UBE) surgery is an innovative minimally invasive technique for treating lumbar disc herniation. However, conventional surgical positioning, which combines preoperative surface localization with intraoperative fluoroscopy, has several limitations, including suboptimal accuracy, procedural complexity, and reduced operative efficiency. Additionally, incomplete decompression and over-decompression are common issues in UBE surgery, might leading to disastrous outcomes. However, determining the extent of laminectomy remain a significant challenge. This study explores the use of Kirschner Wire as a localization tool in UBE surgery to enhance localization precision and the the appropriate decompression range. This study included 78 patients diagnosed with lumbar disc herniation (LDH) and radicular pain who underwent UBE discectomy using Kirschner Wires as a localization tool. Another 73 patients with LDH underwent standard UBE discectomy without Kirschner Wires. We compared demographic data, surgical variables, postoperative complications, and health-related quality of life (HRQOL) between the two groups. Incorrect segmental localization occurred in 2 patients in the Kirschner Wire group and 11 patients in the standard UBE discectomy group, indicating a significant difference. The Kirschner Wire group demonstrated shorter total operation time, less time spent identifying the correct segment, fewer instances of radiology exposure, and reduced intraoperative blood loss. Additionally, less paraspinal muscle injury was observed in the Kirschner Wire group. Incomplete decompression was identified in 4 patients in the standard UBE discectomy group, all of whom required revision surgery, whereas no cases of incomplete decompression were observed in the Kirschner Wire group. The incidence of facet injury was higher in the standard UBE discectomy group due to the over-decompression. However, no significant differences were found between the groups in terms of dural tear, root injury, incision infection, and revision surgery. Both groups showed improvements in visual analog scale (VAS) scores for back pain, VAS scores for leg pain, and Oswestry Disability Index (ODI), with a more significant decrease in leg pain VAS scores observed in the Kirschner Wire group. Kirschner Wire is an effective localization tool in UBE discectomy, providing accurate segmental localization and aiding surgeons in determining the extent of laminectomy for decompression, thus reducing the likelihood of incomplete decompression or over-decompression. Additionally, the use of Kirschner Wire can decrease total operation time, radiation exposure, intraoperative blood loss, and paraspinal muscle injury. We recommend Kirschner Wire as localization tools in UBE discectomy to enhance surgical precision and outcomes.